Field Trial of Primary and Booster Dose of Inactivated Vaccine Against Bovine Respiratory Bacteria in Young Holstein Calves - Mori, Kazusa (J Vet Res, 2020)
INTRODUCTION: The objective of this research was to evaluate the antibody response to multiple doses of an inactivated mixed vaccine against Histophilus somni, Pasteurella multocida, and Mannheimia haemolytica, and to investigate the influence of age at time of vaccination in the field. MATERIAL AND METHODS: Healthy female Holstein calves received the vaccine at the age of 5–12 days and 2, 3, or 4 weeks later in the first experiment or at 1, 2, or 3 weeks of age and 4 weeks later in the second. Blood samples were collected at each vaccination and 3 weeks after the booster dose. Based on the antibody titres after the vaccinations, calves were divided into positive and negative groups for each of the bacteria. Calves in the control group were vaccinated only once at the age of 19–26 days. RESULTS: Antibody titres against H. somni and P. multocida were significantly increased by the booster. After the second vaccinations, the titres against each bacterium were higher than those of the control group, and the M. haemolytica-positive percentage in calves with high maternal antibody levels (MAL) exceeded that in calves with low MAL. In the first experiment, a majority of the M. haemolytica-positive calves tended to have received the primary dose at seven days of age or older. CONCLUSION: A booster dose of the inactivated bacterial vaccine in young Holstein calves increased antibody production and overcame the maternal antibodies. Calves should be vaccinated first at seven days of age or older.